Synthesis and Spectral Studies of 4,4'-(Hydrazine-1,2-diylidenedimethylylidene)-bis-(2-methoxyphenol) and Its Transition Metal Complexes with Promising Biological Activities - Rani, Anita; Kumar, Manoj; Tuli, Hardeep Singh; Abbas, Zahoor; Prakash, Vinit (Asian Journal of Chemistry, 2020)
The study describes the synthesis, characterization and biological activity of a novel Schiff base ligand and its transition metal complexes. The Schiff base ligand was obtained by a condensation reaction between 4-hydroxy-3-methoxybenzaldehyde (p-vanillin) and hydrazine hydrate using ethanol as solvent. A new series of Ni(II) and Fe(III) complexes were also derived by reaction of prepared Schiff base ligand with NiCl2 and FeCl3. Both the ligand and its metal complexes were characterized by solubility, melting point and elemental analysis. These compounds were further identified by analytical techniques, FTIR, NMR and mass spectrometry. The ligand and its transition metal complexes were also subjected to in vitro biological activities i.e. antimicrobial, antiangiogenic and DNA photo cleavage. For antimicrobial activity compounds were tested against two strains of bacteria and two strains of fungi. Different concentrations of prepared compounds were treated with fertilized chicken eggs and plasmid DNA to find out antiangiogenic and DNA photocleavage activity, respectively.